De l’engagement collectif à la parole éclatée : une étude sur les mécanismes du silence après Gênes 2001 - François Dumasy (Laboratoire Italien)
Based on interviews conducted twenty years after the event, this article examines how the Genoa G8 counter-summit in 2001 has been a driving force behind new forms of mobilization, bringing together activists most of whom had no real militant background. Focusing on the French collective Aarrg, the author examines the correlation between the preparation of demonstrations, the experience of on-site repression and the difficulty of expressing members’ feelings, leading to an exhaustion of the group’s capacity to elaborate a collective word that would allow the expression of individual affects. The article also seeks to assess the long-term consequences of this brief episode of commitment, in order to question the biographical effects of this mobilization and the silences that followed it, highlighting the effects of the gap between the Italian and French terrains and questioning the mechanisms of personal concealment in the transmission of collective experiences.